Daya Tarik dan Analisis Representasi Visual pada Kover Album Shinee “The Story Of Light” - Khairunnisa, Anida Putri; Sucitra, I Gede Arya (Institut Seni Indonesia Yogyakarta, 2025)
The album cover not only functions as a record protector, but also as an intermediary in conveying the message of the musical work itself. As a contemporary band, SHINee employs the album cover as a paratext, enabling fans to engage with the music through audiovisual interpretation. This research analyzes and explains the meaning behind each of the visual elements presented. The purpose of this study is to determine the appeal of album covers and identify the components of cover artwork representations contained in SHINee album covers. This research employs a qualitative methodology, spesifically descriptive analysis, to elucidate the symbolic, chromatic, compositional, and other design elements through the lens of Stuart Hall’s representation theory. Based on the analysis of the appeal of album covers and identify the components of cover artwork representations contained on SHINee’s album cover, it is know that the visual composition as the attractions is dominated by geometric shapes and figures, as well as the use of primary and contrasting colors. The visual style uses a minimalist and pop art approach to portray simplicity. The symbols interpreted from the related visual elements (geometric shapes, figures, colors) use approaches from K-Pop and Obangsaek. Kover album tidak hanya difungsikan sebagai pelindung rekaman, namun juga sebagai perantara dalam menyampaikan pesan dari karya musik itu sendiri. SHINee sebagai band kontemporer menggunakan kover sebagai parateks yang memungkinkan penggemar untuk menginterpretasi musik secara audiovisual. Penelitian ini menganalisis dan menjelaskan mengenai makna di balik setiap elemen-elemen visual yang disajikan. Tujuan penelitian ini adalah untuk mengetahui daya tarik kover dan komponen representasi karya seni pada kover album SHINee. Pendekatan kualitatif deskriptif analitis digunakan dalam penelitian ini untuk menginterpretasikan simbol, warna, komposisi, dan elemen desain lainnya dengan menggunakan teori representasi Stuart Hall. Berdasarkan hasil analisis daya tarik dan komponen representasi pada kover album SHINee diketahui bahwa komposisi visual sebagai daya tarik kover album SHINee didominasi dengan bentuk geometri dan figur, serta penggunaan warna primer dan kontras. Gaya visualnya menggunakan pendekatan minimalis dan pop art untuk menggambarkan kesederhanaan. Simbol-simbol yang diinterpretasikan (bentuk geometris, figur, warna) menggunakan pendekatan dari budaya K-Pop dan Obangsaek.